Applicability of Smeral’s Model in Explaining Tourism Share of Member States in SAARC Region - Paudyal, Shoorabeer (NRB Economic Review, 2003)
This paper attempts, with help of Smeral Model, to study the determinants of demand share of individual member states in total SAARC arrivals from seven major tourism markets. Empirical study of the tourism with the help of modified version of this model demonstrates the interdependency among the SAARC countries. This study found that relative price and regional share are two important link factors for the individual states in the region. Individual share of the tourism increases with an increase in regional share in the world tourism and with a decrease in relative price of tourism and vice-versa.